2013
DOI: 10.1111/j.2047-2927.2013.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of galectin-3 binding ligands and characterization of galectin-3 proteolytic cleavage in human prostasomes

Abstract: Galectin-3 is a multi-functional carbohydrate binding protein that was previously characterized as a proteolytic substrate for prostate specific antigen (PSA) and was shown to be associated with prostasomes in human semen. Prostasomes are exosome-like vesicles that are secreted by the prostatic epithelium and have multiple proposed functions in normal reproduction and prostate cancer. In the current study, galectin-3 binding ligands in human prostasomes were identified and characterized with the goal to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(73 reference statements)
1
20
0
1
Order By: Relevance
“…Finally, affinity capture chromatography, coupled with LC‐MS/MS, identified KLK3 to interact with galectin‐3 on the surface of prostate‐expressed vesicles, or “prostasomes,” in seminal fluid. Galectin‐3 was confirmed as a novel KLK3 proteolytic substrate and proteolysis of this glycoprotein in seminal fluid was reduced following proteolytic inhibition of KLK3, hence galectin‐3 appears to be a definitive biological KLK3 substrate . This study constitutes another example where identification of a KLK substrate was determined in a reverse manner by a global screening approach used to identify binding proteins of what was eventually found to be a KLK substrate.…”
Section: Proteomics As a Tool For Global Analysis Of Klk Production Amentioning
confidence: 90%
“…Finally, affinity capture chromatography, coupled with LC‐MS/MS, identified KLK3 to interact with galectin‐3 on the surface of prostate‐expressed vesicles, or “prostasomes,” in seminal fluid. Galectin‐3 was confirmed as a novel KLK3 proteolytic substrate and proteolysis of this glycoprotein in seminal fluid was reduced following proteolytic inhibition of KLK3, hence galectin‐3 appears to be a definitive biological KLK3 substrate . This study constitutes another example where identification of a KLK substrate was determined in a reverse manner by a global screening approach used to identify binding proteins of what was eventually found to be a KLK substrate.…”
Section: Proteomics As a Tool For Global Analysis Of Klk Production Amentioning
confidence: 90%
“…The subsequent supernatant was ultracentrifuged at 100,000 g at 4°C for 2 hr to remove membrane and particulate material. Recombinant human galectin‐3 was covalently bound to cyanogen bromide‐activated Sepharose (Sigma, St. Louis, MO, USA) following the manufacturer's instructions, and galectin‐3 affinity column chromatography was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Prostasomes are exosome‐like vesicles in seminal plasma that are secreted by the prostatic epithelium and are proposed to have immunomodulatory functions in the female reproductive tract . We characterized galectin‐3 binding ligands in human prostasomes and demonstrated that galectin‐3 is a proteolytic substrate for prostate‐specific antigen (PSA) in seminal plasma and on the surface of prostasomes . We now report the results of a proteomic study that investigated galectin‐3 function in seminal plasma by characterizing proteins that bound to immobilized galectin‐3.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that CLU binds specifically to disrupted areas of the barrier. CLU was identified as an interacting candidate in a recent proteomics screen for potential LGALS3 interacting proteins from human prostasomes [179].…”
Section: Ocular Surface Barrier Function In Dry Eye Diseasementioning
confidence: 99%